ANALISIS LINGKUNGAN FISIK DAN KARAKTERISTIK INDIVIDU DENGAN FAAL PARU PEKERJA INDUSTRI KERUPUK BAWANG X KEDIRI - Salsabila Al Firdausi; R Azizah (Universitas STRADA Indonesia, 2016)
The quality of the physical environment associated with high levels of dust, temperature, humidity, light, condition of walls, floors, vents, ceilings, as well as the burning chimney can affect workers' health. Crackers industry has the potential disruption workers pulmonary function. This study aims to determine the relationship between the physical environment and the ch aracteristics of individuals with pulmonary function status of workers. This study used cross sectional analytic models. Collecting data of individual characteristics with questionnaires, lung function with spirometry test, physical environments by laboratory testing and direct observation. The results showed all workers using PPE at work, the majority of workers do not smoke period of 2-3 years of work, the status of elementary education, the status of normal BMI, long working day 5 hours. Physical environmental conditions unfavorable, parameters that do not qualify KMK 1405 on Requirements Environmental Health Office Work and Industry is the dust levels, temperature, light, conditions dirty walls, floors slippery, dirty roof and ceiling unavailability. Com ponents that qualify are the ventilation and the presence of the chimney. 2 people working impaired lung function restriction. Individual characteristics are supported by the quality of the physical environment is not good enough relationship status provid es workers pulmonary function, due to the length of employment of less than 5 years